2019
DOI: 10.1177/0894439319859590
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Sense of Community and Continuance Intention in Virtual Communities: The Role of Commitment and Type of Community

Abstract: Virtual communities (VCs) have become essential in current organizations and society, and so their sustainability is a topic of interest for researchers and practitioners. We focus on the sense of virtual community (SoVC) and commitment as relevant antecedents in achieving the success and maintenance of different types of VCs (communities of interest, virtual learning communities, and VCs of practice). Specifically, this study examines a moderated mediation model in which the type of VC moderates the indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
0
8
0
1
Order By: Relevance
“…Thus, we respond to the call to study how well-being develops in virtual teams [4], with particular emphasis on the role of TWE as a proxy for eudaimonic well-being [3,4]. Considering the digitalization of work and life [7,120,121], especially since the disruption caused by the COVID-19 health crisis [9], there is a need for sustainable teamwork. Moreover, sustainability in virtual environments is still an unfolding topic (e.g., [121]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we respond to the call to study how well-being develops in virtual teams [4], with particular emphasis on the role of TWE as a proxy for eudaimonic well-being [3,4]. Considering the digitalization of work and life [7,120,121], especially since the disruption caused by the COVID-19 health crisis [9], there is a need for sustainable teamwork. Moreover, sustainability in virtual environments is still an unfolding topic (e.g., [121]).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the digitalization of work and life [7,120,121], especially since the disruption caused by the COVID-19 health crisis [9], there is a need for sustainable teamwork. Moreover, sustainability in virtual environments is still an unfolding topic (e.g., [121]). Thus, to develop sustainable virtual teams, prior research highlighted the importance of focusing on engagement [16,41,49].…”
Section: Discussionmentioning
confidence: 99%
“…It motivates the members to make the transaction with a specific brand (Chiang et al, 2018); brand trust is the other most vital determinant in online shopping. The influence of SOVC reflects the buying pattern of consumers (González-Anta et al, 2021); the brand's image dictates the trade, as the feedback established for a seller will either boost or knock down the sales, dependent upon the reviews from the buyers of the community.…”
Section: Sense Of Virtual Community and Brand Trustmentioning
confidence: 99%
“…With the rapid development of information technology, the variety of virtual communities is increasing (Blanchard, 2008;Abfalter et al, 2012;McLoughlin et al, 2018;González-Anta et al, 2019). As a professional virtual community, the virtual academic community meets the new needs of scholars for academic cooperation in the network environment.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic and extrinsic motivations, social capital factors and knowledge sharing outcomes are crucial factors. González-Anta et al (2019) examine a moderated mediation model and show that relationship and commitment was higher for communities of interest and virtual learning communities than for virtual communities of practice. Peñarroja et al (2019) analysed the influence of facilitating conditions on the effectiveness of a virtual community of practice and found that the perceived usefulness and perceived ease of use moderated the effects of facilitating conditions on effectiveness through a sense of virtual community.…”
Section: Introductionmentioning
confidence: 99%